The rise and fall of the Communist Party of Iraq - Ismael, Tareq Y. (New York : Cambridge University Press, 2008)
This comprehensive work examines the complex transformation of the Iraqi Communist Party from vanguard actor under Iraq's conservative monarchy to rearguard lackey under US occupation. Born in the interlude between two world wars, the Communist Party of Iraq was fostered by Iraq's embryonic intelligentsia as an approach to national liberation during the period of British domination. Driven underground or into exile by successive waves of Baathist repression beginning in 1963, the party's leadership became progressively dependent on and subservient to the Soviet Union. Dissatisfied with the party's irrelevance to Iraq's sociopolitical dynamics, reform efforts were thwarted by the old-guard leadership, and in the mid-1970s the party fragmented. With the fall of the Hussein regime and the US occupation of Iraq in 2003, the remnants of the party's old guard connected with the US-installed government and became part of the US project in Iraq.